Assessing the Risks of China’s Medical Tourism from the Legal Perspective - Shen X; Qu Y; Wu Q (Dove Medical Press, 2020)
Xince Shen,1 Yunfeng Qu,1 Qiuzi Wu2 1School of Law, Hainan University, Haikou, Hainan, People’s Republic of China; 2Graduate Institute of Interpretation and Translation, Beijing Foreign Studies University, Beijing, People’s Republic of ChinaCorrespondence: Xince ShenSchool of Law, Hainan University, No. 58 Renmin Road, Meilan District, Haikou City, Hainan Province, People’s Republic of ChinaEmail shlxce@foxmail.comAbstract: While China’s medical tourism industry is increasingly standardized and institutionalized, the relevant research assessing its legal risks is still absent. This paper aims to evaluate the risks of medical tourism from the legal perspective by exploring the conflict between the developing new practice and the existing legal system, summarizing the legal risks in medical tourism, and proposing measures and suggestions to mitigate such risks. The empirical research method is employed to review the legal risks in Boao Lecheng International Medical Tourism Pilot Zone, which is the pioneering project of China’s development within the medical tourism industry. These research methods include collecting the latest medical tourism policies and regulations, judicial decisions, and on-the-spot investigation of the Pilot Zone. It is found that the legal risks in medical tourism activities are mainly concentrated in the administrative, civil and litigious legal relations, and concern four major subjects which are regulators, medical operators, tourism operators and consumers. For regulators, their administrative supervision has not been well in place before and during medical tourism activities, and there remain legal gaps in regulation. In terms of the protection of consumers’ substantive rights, service providers and operators may evade their responsibilities by exploring the vacuum area during the transition from the old laws to the new ones, and the conflicting provisions exist between the special laws and general ones. Concerning the protection of consumers’ litigation rights, there are many obstacles for consumers to safeguard their interests through litigation in a foreign land. In this paper, medical tourism activities are identified among four legal subjects and involving three types of legal risks, in the hope to help improve the overall understanding of medical tourism from the legal perspective, and put forward targeted suggestions on the potential legal risks.Keywords: medical tourism, legal risk, Boao Lecheng International Medical Tourism Pilot Zone, Free Trade Port